Primary healthcare nurses' perceptions about their ability to utilise electronic health records - Tengeh, Laura Ngweh (Obzornik zdravstvene nege, 2022)
ntroduction: The implementation, adoption and use of electronic health records remains a global challenge despite the numerous advantages associated with their use. This paper explores primary healthcare nurses' perceptions regarding their skill levels in using EHRs.Methods: Data were collected using a self-administered questionnaire from a sample of 71 nurses (63% response rate) in selected primary health care (PHC) facilities of the Northern-Tygerberg substructure, Cape To w n .Results: The overall results show that 59 respondents (83%) believed that they were skilled in using EHRs in PHC. Nearly two thirds of all nurses (46 or 64.8%) reported using EHRs for nursing documentation, 45 nurses (63%) reported using EHRs to store, retrieve and transfer data, 44 (62%) reported being able to design a flow chart, 38 (53.5%) reported being able to access databases and 38 (52.1%) reported being able to convert electronic files for various applications. However, 33 nurses (46.5%) were unsure of their computer skills in creating multimedia files. This varied from service department to service department, with 62 respondents (87.3%) in pediatric care and 59 respondents (83.1%) in family planning, adult nursing and HIV management reporting having EHR skills. Enrolled nurses rated their EHR skills significantly lower (58%) than registered nurses (92%) (p = 0.028).Discussion and conclusion: Although most respondents in this study reported being skilled in using EHRs in PHC, better computer accessibility and continuous training are importantongoing requirements. Further qualitative research is needed to better understand some of the problems and barriers which affect nurses' ability to use EHRs in PHC settings.
Keywords: electronic health records; elektronske zdravstvene kartoteke; medicinske sestre; nurses; perceived skills; primarno zdravstveno varstvo; primary health care; samoocena sposobnosti